2020
DOI: 10.3390/ijms21176233
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Regions of Prion Protein: Functions and Roles in Prion Diseases

Abstract: The normal cellular isoform of prion protein, designated PrPC, is constitutively converted to the abnormally folded, amyloidogenic isoform, PrPSc, in prion diseases, which include Creutzfeldt-Jakob disease in humans and scrapie and bovine spongiform encephalopathy in animals. PrPC is a membrane glycoprotein consisting of the non-structural N-terminal domain and the globular C-terminal domain. During conversion of PrPC to PrPSc, its 2/3 C-terminal region undergoes marked structural changes, forming a protease-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 102 publications
0
15
0
Order By: Relevance
“…126-230) has a highly conserved, mostly helical tertiary structure, with one intramolecular disulfide bond [33,34]. The unstructured N-terminal half possesses several regions involved in specific functions [35]. Among them, the highly conserved hydrophobic domain (HD, aa.…”
Section: Introductionmentioning
confidence: 99%
“…126-230) has a highly conserved, mostly helical tertiary structure, with one intramolecular disulfide bond [33,34]. The unstructured N-terminal half possesses several regions involved in specific functions [35]. Among them, the highly conserved hydrophobic domain (HD, aa.…”
Section: Introductionmentioning
confidence: 99%
“…1). The FT region, an intrinsic disordered domain, plays a crucial role in the pathogenesis of prion diseases (15). The primary nine polybasic amino acids (23)(24)(25)(26)(27)(28)(29)(30)(31) have been reported as a prerequisite for channel activity of the truncated PrP protein (∆CR PrP with 105-125 amino acids deleted) (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several studies have shown that the NPR-which is located at very Nterminus and remains PK-sensitive in PrP Sc -plays a significant role in the pathogenesis of prion disease (21). Several transgenic mice expressing PrP with NPR deletion mutations (oror replacement mutations (replacing 23 KKRPK 28 to J o u r n a l P r e -p r o o f 5 KQHPH or AARPA) were established.…”
Section: Introductionmentioning
confidence: 99%